GraParT: A MATLAB Toolbox for partitioning directed graphs - CİHAN, ONUR (My University, 2021)
Consensus algorithms are increasingly used in multi-agent systems due to their advantages in various applications. Recent results on consensus algorithms show that the number of groups formed in a network of agents utilizing consensus-based algorithms can be computed once its primary and secondary layer subgraphs are determined. In this study, we present GraParT -Graph Partitioning Toolbox- that can be used to partition directed graphs by determining its primary and secondary layer subgraphs and the vertices therein. The toolbox helps the user to build, modify, analyze and illustrate directed graphs in terms of the grouping behavior of the consensus algorithms with its user-friendly interface. GraParT is an open-source software that is available free of charge for academic and non-commercial use
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); directed graphs; consensus algorithms; group consensus; MATLAB toolbox